2018
DOI: 10.3390/w10030279
|View full text |Cite
|
Sign up to set email alerts
|

Using Sap Flow Data to Parameterize the Feddes Water Stress Model for Norway Spruce

Abstract: Abstract:Tree water use is a key variable in forest eco-hydrological studies and is often monitored by sap flow measurements. Upscaling these point measurements to the stand or catchment level, however, is still challenging. Due to the spatio-temporal heterogeneity of stand structure and soil water supply, extensive measuring campaigns are needed to determine stand water use from sap flow measurements alone. Therefore, many researchers apply water balance models to estimate stand transpiration. To account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 75 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…This means, that the vast majority of isotope based RWU studies is based on graphic or statistical methods, which allow a description of observations but abstain from offering physically-based models, which could be used to predict the reaction of RWU to changing environmental conditions. Lv (2014), Rabbel et al (2018) and Brinkmann et al (2018) have modelled RWU of trees with implementations of a Feddes-style RWU model described by Feddes et al (1976) and Jarvis (1989) as implemented within the soil hydrological model HYDRUS-1D (Šimůnek et al, 2008). Even though the Feddes RWU model was originally developed to model water uptake of agricultural crops, the above listed applications demonstrated that Feddes RWU models are also suited to simulate RWU of mature trees.…”
Section: Water Uptake and Tree Isotope Modellingmentioning
confidence: 99%
“…This means, that the vast majority of isotope based RWU studies is based on graphic or statistical methods, which allow a description of observations but abstain from offering physically-based models, which could be used to predict the reaction of RWU to changing environmental conditions. Lv (2014), Rabbel et al (2018) and Brinkmann et al (2018) have modelled RWU of trees with implementations of a Feddes-style RWU model described by Feddes et al (1976) and Jarvis (1989) as implemented within the soil hydrological model HYDRUS-1D (Šimůnek et al, 2008). Even though the Feddes RWU model was originally developed to model water uptake of agricultural crops, the above listed applications demonstrated that Feddes RWU models are also suited to simulate RWU of mature trees.…”
Section: Water Uptake and Tree Isotope Modellingmentioning
confidence: 99%
“…Sap flow instruments are widely used for the estimation of whole-plant water use and transpiration [3][4][5]. The accuracy of sap flow measurements and the upscaling of these to the whole-plant water use relies on the knowledge of species-specific physiological characteristics, as well as on information of radial and circumferential patterns of sap velocity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, measurements of δ xyl and isotopic compositions of soil water (δ soil ) usually required the laborious extraction of the respective waters. Scholander pressure chambers (Scholander et al, 1965) can be used to extract xylem water from branches (Rennenberg et al, 1996;Magh et al, 2020). Another common xylem water extraction method is cryogenic vacuum extraction (Dawson and Ehleringer, 1991;Orlowski et al, 2013;Newberry et al, 2017), which is also commonly used for soil pore water extraction (Dalton, 1988).…”
Section: Measurement Of Soil and Xylem Water Isotopesmentioning
confidence: 99%